2017
DOI: 10.18325/jkmr.2017.27.3.61
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Korean Medicine Treatment after Musculoskeletal Disorder Surgery: A Literatural Review

Abstract: Objectives The purpose of this review is to analyse the trend in papers related with Korean Medicine Treatment after musculoskeletal disorder surgery. Methods We reviewed Korean Medicine papers by searching Korean web databases 'Korea Traditional Knowledge Portal', 'Scientific and Technological Information Integration Service (NDSL)', 'Academic Research Information Service (RISS)', 'Korea Medical Informati on Portal (OASIS)'. We classified the papers by the year of publishment, the title of journals, the type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
3
0
9
Order By: Relevance
“…And although the surgery of the tear itself may be successful, the postoperative treatment may be inadequate, resulting in pain or stiffness after the surgery. (1) Korean Medicine (KM) utilizes herbal medicine, acupuncture, physical therapy, in addition to pharmacopuncture and Chuna therapy to rehabilitate the patients after musculoskeletal surgeries (7). Kim,et al (8) reported no significant difference in terms of pain control in the treatment group that only used KM rehabilitation therapy and the treatment group that used combination therapy with an analgesic.…”
Section: Introductionmentioning
confidence: 99%
“…And although the surgery of the tear itself may be successful, the postoperative treatment may be inadequate, resulting in pain or stiffness after the surgery. (1) Korean Medicine (KM) utilizes herbal medicine, acupuncture, physical therapy, in addition to pharmacopuncture and Chuna therapy to rehabilitate the patients after musculoskeletal surgeries (7). Kim,et al (8) reported no significant difference in terms of pain control in the treatment group that only used KM rehabilitation therapy and the treatment group that used combination therapy with an analgesic.…”
Section: Introductionmentioning
confidence: 99%
“…[15] There are some reported cases of postoperative pain therapy and rehabilitation in Korean medicine, but there is a lack of systematically organized domestic studies. [16] Therefore, the authors aim to perform a systematic review of studies examining the effects of herbal medicine treatment on postoperative pain.…”
Section: Introductionmentioning
confidence: 99%
“…침치료는 의과의 수술적 치료와 비교하여 경제성과 안 전성의 이유로 임상에서 널리 사용되며, 비만의 치료로 사 용되는 침치료에 대한 많은 연구가 이루어지고 있다 11,12) . 19,20) , 2010년 2편 21,22) , 2013년 1편 23) , 2014년 2편 24,25) , 2015년 1편 26) , 2016년 2편 27,28) , 2017년 1 편 29) , 2018년 2편 30,31) , 2019년 1편 32) , 2021년 1편 33) , 2022년 1편 34) , 2023년 2편 35,36) 이 발표되었다.…”
unclassified